Fixed Point Results for an Almost Generalized α-Admissible Z-Contraction in the Setting of Partially Ordered b-Metric Spaces - Solomon Gebregiorgis Teweldemedhin; Kidane Koyas Tola (Abstract and Applied Analysis)
In this paper, we introduce an almost generalized α-admissible Z-contraction with the help of a simulation function and study fixed point results in the setting of partially ordered b-metric spaces. The presented results generalize and unify several related fixed point results in the existing literature. Finally, we verify our results by using two examples. Moreover, one of our fixed point results is applied to guarantee the existence of a solution of an integral equation.